Pengembangan E-modul Berbasis CIRCSA pada Materi Virus untuk Melatih Berpikir Kritis dan Literasi Ilmiah Siswa - Irmasari, Eliyan; Marianti, Aditya; Martuti, Nana Kariada Tri; Riawan, Awinda Sari (Universitas Negeri Surabaya, 2023)
Developing technology-based teaching materials, such as e-modules, is an effective method for training students' thinking abilities, such as critical thinking and scientific literacy. Objective: This research aims to assess the characteristics, feasibility, and students’ responses to developing an e-module of viral material based on the CIRCSA learning model. Method: The ADDIE development framework, including analysis, design, and development, was used to conduct this research. The scope of this research is limited to assessing the feasibility of the CIRCSA-based e-module characteristics, materials, media, and students’ responses on small-scall trials. Results: Data analysis revealed that the CIRCSA-based e-module that integrates critical thinking and scientific literacy achieved an very valid criterion. The feasibility of materials and media obtained a very valid category. Additionally, students' responses to the e-module usage resulted in a very good category. Novelty: Developing CIRCSA-based e-modules to improve students' critical thinking and scientific literacy has never been done before.